2016
DOI: 10.1371/journal.pone.0157249
|View full text |Cite
|
Sign up to set email alerts
|

Return of spontaneous Circulation Is Not Affected by Different Chest Compression Rates Superimposed with Sustained Inflations during Cardiopulmonary Resuscitation in Newborn Piglets

Abstract: ObjectiveRecently, sustained inflations (SI) during chest compression (CC) have been suggested as an alternative to the current approach during neonatal resuscitation. However, the optimal rate of CC during SI has not yet been established. Our aim was to determine whether different CC rates during SI reduce time to return of spontaneous circulation (ROSC) and improve hemodynamic recovery in newborn piglets with asphyxia-induced bradycardia.Intervention and measurementsTerm newborn piglets were anesthetized, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 35 publications
6
41
0
Order By: Relevance
“…Further animal studies by our group compared CC rates of 90/min and 120/min with similar time of ROSC 14. During CC carotid blood flow, mean arterial pressure, and % change in ejection fraction and cardiac output were higher in the CC+SI 90/min group compared with CC+SI 120/min 14. This further supports that higher CC rates do not improve systemic perfusion and that the current recommendation of 90 CC per minute are sufficient to achieve systemic perfusion.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Further animal studies by our group compared CC rates of 90/min and 120/min with similar time of ROSC 14. During CC carotid blood flow, mean arterial pressure, and % change in ejection fraction and cardiac output were higher in the CC+SI 90/min group compared with CC+SI 120/min 14. This further supports that higher CC rates do not improve systemic perfusion and that the current recommendation of 90 CC per minute are sufficient to achieve systemic perfusion.…”
Section: Discussionsupporting
confidence: 56%
“…However, the study used a higher rate during CC+SI which might have contributed to the faster ROSC. Further animal studies by our group compared CC rates of 90/min and 120/min with similar time of ROSC 14. During CC carotid blood flow, mean arterial pressure, and % change in ejection fraction and cardiac output were higher in the CC+SI 90/min group compared with CC+SI 120/min 14.…”
Section: Discussionmentioning
confidence: 83%
“…Aaltonen et al (34) speculated that this drop in MAP could not be explained by a reduced left ventricular output. This is supported by results from Li et al (35) that cardiac output in asphyxiated newborn piglets after CPR was not different from control piglets. Thus, a more likely reason for hypotension in the asphyxic neonate is the profound acidosis and lack of substrate (ATP).…”
Section: Discussionsupporting
confidence: 79%
“…This is a plausible explanation for why attempts at increasing coronary perfusion by increasing the C:V ratio or even CC rate has not been successful in models of perinatal asphyxia. CCaV has not proven to be of benefit in asphyxiated piglets, unless they are combined with a sustained inflation (35, 37). Manikin studies support that continuous CC and asynchronous standard positive pressure ventilation might not provide benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical model has also suggested that higher CC rates (as high as 180/min for term infants) could optimize systemic perfusion [10]. A recent randomized animal trial comparing CC+SI using CC rates of 90/min versus 120/min reported a similar time to ROSC and survival rate, and similar hemodynamic and respiratory parameters during CPR [17], suggesting that higher CC rates are not necessarily an advantage. In addition, recent simulation studies assessing fatigue reported that operators using CC rates of 120/min compared to 90/min showed signs of fatigue within 2 min of initiating CC [18,19].…”
Section: Discussionmentioning
confidence: 99%